Interfaith Marriage in Indonesia: Juridical Challenges and Human Rights Perspectives - Ais Surasa; Ramdani Wahyu Sururie; Najib A. Gisymar; Mohammad Syaiful Aris; Diana Farid; Muhammad Husni Abdulah Pakarti (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
Interfaith marriage refers to a union between two individuals who adhere to different religions and remains a complex issue within the Indonesian legal system. Legally, Law No. 1 of 1974 on Marriage does not explicitly regulate interfaith unions. However, Article 2(1) of the law states that a marriage is valid if conducted by the religious laws and beliefs of the parties involved. This commonly means that interfaith marriages lack legal recognition in Indonesia. This interpretation is further reinforced by the issuance of Supreme Court Circular Letter (SEMA) No. 2 of 2023. This study adopts a normative juridical method with a descriptive qualitative approach. Primary data were obtained from the Marriage Law, the Compilation of Islamic Law, fatwas issued by the Indonesian Ulema Council (MUI), Muhammadiyah, Nahdlatul Ulama (NU), and SEMA No. 2 of 2023. Secondary data were gathered from legal literature, court decisions, and scholarly articles. The findings indicate that, under Article 2(1) of the Marriage Law, interfaith marriages are deemed invalid under Indonesian national law. However, from a human rights perspective—as stipulated in Article 16 of the Universal Declaration of Human Rights (UDHR) and Article 28B(1) of the 1945 Constitution—every individual has the right to marry regardless of religious affiliation. This study also outlines several legal alternatives available to interfaith couples seeking to formalize their marriage, including filing a court petition, temporarily adhering to one partner’s religious law, or marrying abroad. The legal implications of interfaith marriage include issues related to its validity, administrative registration, children's legal status, and both spouses' civil rights.